Walking the Tightrope of Job Demands and Resources: Leveraging Work Engagement to Counter Turnover Intentions of Information Technology Professionals - Van Heerden, Jana; Du Plessis, Marieta; Becker, Jurgen R. (Frontiers in Psychology, 2022)
Organisations within the banking industry are increasingly confronted with attraction and retention challenges within their Information Technology (IT) divisions, driven by an increase in demand for skilled resources within the market. Therefore, the primary objective of the study was to explore the impact of job resources and job demands on work engagement and employee turnover intentions within the IT division of a South African bank. The Job Demands-Resources (JD-R) model was applied as theoretical framework to identify the unique job resources and job demands driving work engagement and turnover intentions of employees within this highly specialised section of the South African banking industry. Quantitative data was collected from 239 IT professionals via a self-administered, web-based survey measuring work engagement, job demands and resources, and turnover intentions. After confirmation of the factor structures of each of the variables, the direct and indirect relationships between the variables were analysed. The results indicate statistically significant relationships between job resources, work engagement and turnover intentions. Job demands moderated the relationship between job resources and work engagement, whilst work engagement mediated the relationship between job resources and turnover intention. By applying the JD-R model as a theoretical framework for the study, the unique job resources and job demands as drivers of work engagement and turnover intentions of IT employees could be highlighted. This can be used by human capital development practitioners to develop focused work engagement and retention strategies.